Hit or miss? Evaluating the effectiveness of Natura 2000 for conservation of forest bird habitat in Sweden - Ewa H. Orlikowska; Johan Svensson; Jean-Michel Roberge; Malgorzata Blicharska; Grzegorz Mikusiński (Global Ecology and Conservation, 2020)
Biodiversity conservation often requires a landscape perspective. When establishing the Natura 2000 (N2k) network, the effectiveness of the sites and the influence of the surrounding landscapes for species of interest was often disregarded. We analyzed the effectiveness of N2k sites in Sweden for three forest bird species of conservation interest in the European boreal landscapes: lesser spotted woodpecker (LSW), Siberian jay (SJ) and hazel grouse (HG). Our objectives were to: 1) quantify effective suitable habitat area in N2k sites with and without consideration of the adjoining landscapes; 2) examine effective habitat area within N2k sites along the north-south vegetation gradient 3) analyze functionality of N2k sites and assess how forests outside the sites affect habitat suitability inside N2k. GIS-based habitat suitability index models were applied to calculate the amount of effective habitat within and outside N2k sites. N2k sites contributed with 10% (HG), 13% (SJ) and 51% (LSW) suitable habitat identified in Sweden. Functionality of forest environments as habitat was higher inside N2k sites for LSW within all vegetation zones, and for SJ in the Alpine and Middle Boreal zones; for HG habitat outside the sites was more functional in all zones accept Alpine and Middle Boreal. The majority of N2k sites were of quite small size (<500 ha) and the size influenced their functionality for LSW and HG, with larger N2k sites being more functional. For SJ, however, average functionality of N2k sites was not influenced by their size. The largest average habitat increase linked to considering the contribution of areas outside N2k sites for their functionality as habitat was for the N2k sites of smaller size (1-500 ha). Therefore, the presence and quality of forests outside of N2k sites are of a greater importance for smaller sites, and as such these should be carefully managed. To improve conservation efficiency of the N2k sites in Sweden, we call for incorporating them into the development and implementation of the regional Green Infrastructure plans.